Effect of Vibration on the Heat Transfer Process in the Developing Region of Annulus with Rotating Inner Cylinder - Mauwafak A. Tawfik; Akeel A. Mohammed; Hayder Zuhair Zain (Engineering and Technology Journal, 2015)
Experimental investigation has been carried out to study the effect of induced vibration on the heat transfer process in the simultaneously developing of hydrodynamic and thermal boundary layer region of a concentric vertical annulus with uniformly heated outer cylinder and rotating solid inner cylinder.The experimental setup consists of an annulus, which has a radius ratio of 0.365 and outer cylinder with a heated length 1.2 m subjected to the constant heat flux. The investigation covers Reynolds number (Re) range from 514 to 1991, Taylor number (Ta) values are 10.44×104& 82.23×104, heat flux varied from 468 W/m2 to 920 W/m2 and frequency (Fr) values are 32 & 77 Hz. Results showed for all frequency values that the local Nusselt number values increase as the heat flux increases when the value of frequency near the natural frequency and the value of the surface radiation decrease.Correlation equations have been deduced to calculate the rate of heat transfer, represented by the average Nusselt number (Num) as a function of (Ta), (Ra) and (Fr). A comparison has been made between the present work and the previous works for temperature and local Nusselt number variations and it has given a good agreement.